Efeito do ácido linoléico conjugado na sobrevivência pós criopreservação de embriões bovinos produzidos in vitro - Laila Succar Teixeira do Rosario Rahme (2012)
Cryopreservation of bovine embryos produced in vitro is a critical point for the improvement of biotechnical techniques, since it allows the commercial use of embryos. The greatest amount of lipids in the cytoplasm of embryonic cells implies a reduction in quality and freezability of embryos. The present experiment aimed to test the influence of the addition of trans-10, cis-12 conjugated linolei acid (CLA) and / or fetal calf serum to the culture medium on the concentration of intra-cytoplasmic lipids in bovine embryos produced in vitro. It was tested four different culture medium: treatment 1 (T1 - control, 443 oocytes) - SOF medium with fetal calf serum; treatment 2 (T2 - 439 oocytes) - SOF medium with fetal calf serum associated with CLA; treatment 3 (T3-500 oocytes) - SOF medium without fetal calf serum; and treatment 4 (T4 - 496 oocytes) - SOF medium supplemented with CLA. Twelve morulae of each treatment were fixed in the fifth day of culture (D5) for analyzing the concentration of cytoplasmic lipid using the dye Nile Red. On day seven of culture (D7), expanded blastocysts were vitrified using the Open Pulled Straw (OPS), and the culture medium was frozen for analyzing the concentration of peroxide (H2O2) released into the medium, using the kit QuantiChromTM Peroxide Assay Kit (DIOX-250). After 15 days, vitrified embryos were warmed and re-expansion and hatching rates were analyzed. There was no statistical differences (P>0.05) in cleavage rates (46.0%, 51.2%, 49.8%, 51.9% for T1, T2, T3 and T4, respectively). Embryos cultured in the presence of fetal calf serum presented higher rates of blastocysts production (T1 = T2 = 24.2% and 24.2%, respectively) than embryos cultured in serum free medium (T3 and T4 = 16.6% = 15,0%). Embryos cultured in the presence of serum (T1) had higher (P<0.05) increase of lipid droplets in relation to other treatments. The re-expansion and hatching rates were similar among treatments after vitrification. There was no differences (P>0.05) in the concentration of peroxide (H2O2) in the medium among treatments. In conclusion, the presence of fetal calf serum increased the blastocyst yield, but increased the concentration of lipid droplets in the cytoplasm of embryos. The addition of CLA in the medium reduced the concentration of lipids in embryos, but did not increase the hatching rates after vitrification. The presence of CLA in the medium did not increase the concentration of H2O2